Working with teaching assistants and other support staff for inclusive education - Chambers, Dianne (Bingley, U.K. : Emerald, 2015)
Support staff in schools are increasingly recognised as playing an important, though often undefined, role in inclusive education. While there has been some research on how best to work with support staff, this book provides readers with a comprehensive examination of roles and responsibilities within the classroom. Issues in determining appropriate ways to work effectively with support staff are raised, along with strategies teachers can use to enhance the collaborative and reflective nature of working with others.
The changing nature of the roles of support staff / Dianne Chambers -- New metaphors for teacher/paraeducator relationships / Janet Stivers, Sharon Cramer -- The role of psychologists in inclusive settings / Paul A. Bartolo -- Incorporating therapy into the regular curriculum : working together with occupational therapists / Michelle A. Villeneuve, Nancy L. Hutchinson -- Paraeducator voices on inclusive education / Dorotha "Mike" Monfore, Jeremy Lynch, Matthew Erickson -- Teacher views on working with others to promote inclusion / Marianne Mangano -- Support staff and indigenous education / Glenda Cain -- Visiting teachers' perceptions about working with teacher assistants and teachers / Derek Hurrell, Lorraine Day -- Programming and planning within a multifaceted classroom / Ritu V. Chopra, Denise J. Uitto -- Working collaboratively with support staff for inclusive education / M. Alexandra Da Fonte, Andrea M. Capizzi -- Assistive technology and teacher assistants / Dianne Chambers, Richard G. Berlach -- Training programs for teacher assistants / Denise J. Uitto, Ritu V. Chopra -- Reflective practitioners : teachers and support staff reflecting together / Susan Main.
Includes index.
Print version record
Keywords: Education -- Special Education -- Learning Disabilities; Teaching of students with specific learning difficulties / needs; Teachers' assistants -- Training of; Inclusive education